The role and sentencing of women in drug trafficking crime - Harper, Rosalyn L. (Legal and criminological psychology, 2002)
Purpose. There has been a great deal of debate concerning the role and sentencing of drug traffickers. Attention has been paid to the gendered organization of the drug trafficking trade whereby women tend to occupy the high-risk, low-status role of courier. The main aim of our study was to explore the role of women in drug trafficking crime. In addition, a particular interest focused on whether women were sentenced inequitably in comparison to men. Methods. A secondary analysis was carried out of the demographic and sentencing characteristics of 1715 drug traffickers caught smuggling drugs through Heathrow Airport between July 1991 and September 1997. Results. Women were adopting a more dangerous role by being significantly more likely to take the higher-risk, lower-status role of courier. Female couriers were physically carrying more drugs in terms of weight and value than male couriers. In addition, women were statistically more likely to carry Class A drugs rather than Class B. The results did not support claims of inequity in sentencing between men and women, allowing for the nature of the drug and its weight/estimated street value. Conclusions. The results consolidate previous research on the disproportionate number and specific role of women involved in drug trafficking. This role appears to be counter-intuitive given the theories concerning gender stereotyping and criminality.